PERAN GURU BK DALAM MENGEMBANGKAN RASA PERCAYA DIRI SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DI MAN 1 LABUHANBATU UTARA - Henni Andriani (Al-Mursyid : Jurnal Ikatan Alumni Bimbingan dan Konseling Islam (IKABKI), 2020)
This type of research in this thesis is field research in the form of qualitative research that is descriptive in nature. Data sources used to obtain research data are divided into two types, namely primary data sources and secondary data sources. This data collection technique uses data collection tools, namely observation, interviews, documentation. Whilethe data analysis of the results of this study, based on descriptive analysis, the analysis consists of three analytical flows that interact, namely data reduction, data presentation, and  drawing conclusions.In this study the problem formulations are: 1. What is the level of student confidence in MAN 1 Labuhan Batu Utara, 2. What factors cause students' self-confidence in MAN 1 Labuhan Batu Utara, 3. How is the implementation of group guidance services at MAN 1 Labuhan Batu Utara, 4. How is the role of the BK teacher in developing student confidence in MAN 1 Labuhan Batu Utara.Group guidance services are important to be implemented in schools because they are in accordance with various needs of students themselves such as developing student confidence. In accordance with the purpose of group guidance services namely to provide training for students to have the courage to express their opinions in public which then deliver students toachieve learning success as they wish.Keywords : Guidance Counseling, Self Confidence, Group Counseling Services